Effective Communication Strategy in Controlling Tuberculosis in Assisted Area of Puskesmas Setiabudi in 2024 - Efiyanna, Rina; Ulfah, Fitriana; Rabbani, Fairuz Dhia; Fauziah, Miftahul (Politeknik Kesehatan Kemenkes Jakarta II, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Based on Indonesian Health Survey (SKI) 2023, the prevalence of pulmonary tuberculosis according to doctors’ diagnosis reached 0.3% in Indonesia and 0.4% in DKI Jakarta. This study aims to determine effective communication strategies regarding TB control in the Puskesmas Setiabudi’s assisted area in 2024. We used a two group pre- and post-test design with 42 samples. They were divided into two groups and each group received education by using poster or video as medias. Knowledge data was obtained by filling out questionnaires and characteristic data through interviews. Results most of the cadres had secondary education level (84 and 76.5%) and the average age was above 50 years (55.28 and 50.71 years). There was a greater knowledge increase in the group that received education with audiovisual media (0.59) compared to the group that received education with poster (-0.80) after receiving the education. Conclusion is the utilization of audiovisual media in education is a more effective communication strategy in increasing cadre’s knowledge related to TB prevention and control in the Puskesmas Setiabudi’s assisted area in 2024. It is recommended to modify the refresher workshop method by using audiovisual media.